An Examination of the Spanish Translation of the 50-item International Personality Item Pool Big-five Inventory in a Spanish Speaking Peruvian Sample. (2020) - Hughes, David J.; de Olazabal, Daniel Pizarro; Kratsiotis, Ioannis K.; Twumasi, Ricardo; Booth, Tom
Abstract: The International Personality Item Pool (IPIP) five-factor model inventories are widely used for personality research and have been translated into multiple languages. However, the extent of the psychometric assessment of translated scales is variable, often minimal. The lack of psychometric scrutiny is particularly problematic because translation is an inherently complex process. Here, we present a structural analysis of one Spanish translation of the 50-item IPIP five-factor inventory in a sample of Peruvian, non-university educated, working adults ( n = 778). A global confirmatory factor analytic (CFA) model of the a priori five factors failed to fit. So too did single factor models for four of the five factors, the exception being Neuroticism. Fit was improved via use of an exploratory structural equation measurement model, but the resultant solution showed very poor theoretical coherence. So, we explored the data for systematic measurement artefacts and sought to model them to improve the psychometric properties of the scale. Specifically, the pattern of factor loadings suggested that the lack of coherence might be due to the effects of the valence of item wording (i.e., positively or negatively worded items). CFA models including five substantive factors and a series of method factors modelling shared covariance based on item wording, improved fit and coherence. This investigation suggests that unless method factors are explicitly modelled the tested Spanish translation may not be suitable for use in certain Spanish-speaking countries or samples composed of non-university educated participants. More broadly, the study has implications for many translated scales, especially when used without thorough psychometric evaluation.